A SHORT REVIEW ON BIOLOGICAL APPLICATIONS OF MACROCYCLIC COMPLEXES OF CHROMIUM - Bugalia, swati; Bugalia, Dr Swati; Gurjar, Om Prakash; Saini, Pooja; Kumari, Sushama (Journal of the Chilean Chemical Society, 2023)
ABSTRACT: The main intent of the article is to lay out a brief valuation of biological significance of latest macrocyclic complexes of chromium metal with highlighting the synthesis of these complexes and their applications as antimicrobial agents. Antibiotic ministration is the leading perspective of current medical science which is used to resist infections. But nowadays, power of established drugs against microorganisms is persistently decreased due to bacterial resistivity, which creates a serious issue related to public health. Extensive work has been disclosed on macrocyclic complexes of first row transition metals performing as remedy for copious microbial infections and these reports express their equal or higher capacities to resist the infection as compared to other clinically useable drugs. So here in this review, the synthesized complexes of chromium metal, their precursors and their reported biological activities have been discussed.